Phytochemical Compounds from Laelia furfuracea and Their Antioxidant and Anti-Inflammatory Activities - Abimael López-Pérez; Luicita Lagunez-Rivera; Rodolfo Solano; Aracely Evangelina Chávez-Piña; Gabriela Soledad Barragán-Zarate; Manuel Jiménez-Estrada (Plants)
Laelia furfuracea is an orchid endemic to Oaxaca, Mexico, used for the treatment of cough and has anticoagulant activity. We aimed to evaluate the anti-inflammatory and antioxidant activity of the hydroethanolic extract of L. furfuracea leaves and identify its phytochemical compounds. The leaf material was subjected to solid–liquid extraction. Compounds were identified by UPLC-ESI-qTOF-MS/MS. The Folin–Ciocalteu and aluminum trichloride methods were used to quantify phenols and flavonoids, respectively. The DPPH method was used to determine the antioxidant activity. The anti-inflammatory activity was evaluated in a model of carrageenan-induced plantar edema induced in Wistar rats. Compounds tentatively identified in L. furfuracea leaves were malic, citric, succinic, hydroximethylglutaric, azelaic, eucomic, and protocatechuic acids, saponarin, luteolin-7,3′-di-O-glucoside, isoorientin, and vitexin. The contents of total phenols and flavonoids and antioxidant activity were 394.7 ± 0.1 mg EqAG/g, 129.9 ± 0.005 mg EqQ/g, and 84.6 ± 1.4%, respectively. The anti-inflammatory effect of the extract was dose-dependent, where 1000 µg/paw presented a 43.4% reduction in inflammation, similar to naproxen. The anti-inflammatory and antioxidant effect of the hydroethanolic extract of Laelia furfuracea leaves was demonstrated. This effect may be due to the synergy between its compounds. This orchid is a potential candidate for future pharmacological research due to its anti-inflammatory activity.